The lexical expression of evidentiality: reflection on deduction and event perception - Dall'Aglio Hattnher, Marize Mattos [UNESP] (Federal Univ Ceara, 2018)
The main goal of this paper is to verify the validity of the predictions derived from the stratified approach of the qualificational categories proposed by the Functional Discourse Grammar for the analysis of the lexical expression of evidentiality in Brazilian Portuguese. Different uses of evidential verbs are analyzed, with special attention to polysemic verbs that are used to express two specific evidential subtypes, the perception of an event and the deduction. The results show that the semantic differences between these subtypes are also reflected in the combinatorial between evidentiality and tense, confirming the hierarchical order predicted by the model to grammatical systems of evidentiality.
Keywords: Evidentiality; Evidential verbs; Functional Discourse Grammar